2017
DOI: 10.1302/0301-620x.99b11.bjj-2016-1347.r3
|View full text |Cite
|
Sign up to set email alerts
|

Fixation and clinical outcome of uncemented peri-apatite-coatedversuscemented total knee arthroplasty

Abstract: The tibial components of PA-coated TKAs showed more overall migration compared with the tibial components of cemented TKAs. However, analysis showed that this difference was caused by higher migration of PA-coated components in the first three months, after which a stable migration pattern was observed. Clinically, there was no significant difference in outcome between the groups. Cite this article: 2017;99-B:1467-76.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 30 publications
0
22
0
2
Order By: Relevance
“…Van Hamersveld et al [13] reported in 2018 in a 6-year follow-up RSA study MTPM of 0.9-1.22 mm in 46 cemented tibial components (posterior stabilized TKAs). In 2017 van Hamersveld et al [14] also reported 5-year MTPM results of 0.97 mm of an uncemented peri-apatite coated tibial tray (Triathlon Ò ) and Molt et al [15] found a mean MTPM after 5 years of 0.66-1.1 mm for cemented tibial components, thus leaving our results with 5-year MTPM of 1.8 and 1.4 mm for respectively VR and VP in the upper end of MTPM for both implants.…”
Section: Discussionmentioning
confidence: 99%
“…Van Hamersveld et al [13] reported in 2018 in a 6-year follow-up RSA study MTPM of 0.9-1.22 mm in 46 cemented tibial components (posterior stabilized TKAs). In 2017 van Hamersveld et al [14] also reported 5-year MTPM results of 0.97 mm of an uncemented peri-apatite coated tibial tray (Triathlon Ò ) and Molt et al [15] found a mean MTPM after 5 years of 0.66-1.1 mm for cemented tibial components, thus leaving our results with 5-year MTPM of 1.8 and 1.4 mm for respectively VR and VP in the upper end of MTPM for both implants.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could have been due to early loosening that was not seen radiographically. Radiostereometric analysis (RSA) studies 38,39 have shown significantly higher migration of cementless compared with cemented TKRs. Pijls et al performed a systematic review of RSA studies of TKR migration and concluded that early migration was associated with aseptic loosening 40 .…”
Section: Discussionmentioning
confidence: 99%
“…T he present study was a secondary analysis of all randomized controlled trials (RCTs) involving RSA for the analysis of primary TKAs that were performed in the last 2 decades at 2 centers (Hässleholm, Sweden; Leiden, the Netherlands). Ten published RSA studies including 636 patients undergoing TKA from 2002 to 2016 were pooled (Table I) [12][13][14][15][16][17][18][19][20][21] . Seven studies were conducted in Hässleholm (432 TKAs) [14][15][16][17][18][19][20] and 3 in Leiden (204 TKAs) 12,13,21 .…”
Section: Materials and Methods Designmentioning
confidence: 99%